Factors affecting selection of subcontractors and suppliers by main contractors in Singapore - Xu, Yuqing. (2008)
The objective of this study is to examine the factors that affect the selection of subcontractors / suppliers by the main contractors in Singapore and also to compare the survey results from Hong Kong. An overview of the subcontracting system in the local construction market and literature were presented.